Magnetic Pulse Welding Technology - Jassim, Ahmad K. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
In this paper, the benefits of using Magnetic Pulse machine which is belong to Non-conventional machine instead of conventional machine. Magnetic Pulse Technology is used for joining dissimilar metals, and for forming and cutting metals. It is a non contact technique. Magnetic field is used to generate impact magnetic pressure for welding and forming the work piece by converted the electrical energy to mechanical energy. It is enable us to design previously not possible by welding dissimilar materials and allowing to welds light and stronger materials together. It can be used to weld metallic with non metallic materials to created mechanical lock on ceramics, polymers, rubbers and composites. It is green process; there is no heat, no radiation, no gas, no smoke and sparks, therefore the emissions are negligible.